(untitled) (Texas Journal of Medical Science, 2024)
Over the past years and decades, in the world in general and particularly in Russia, bariatric surgery is becoming more widespread for the treatment of severe forms of obesity. There is an increase in the number of operations performed along with the effectiveness and minimising risks of the operations held due to the improvement of surgical techniques. In this lecture, there are clearly stated indications and contraindications for the surgical treatment of obesity. Here are presented various types of bariatric surgeries and their pathophysiological mechanisms which affect on body weight, carbohydrate and lipid metabolism. There is also presented their effectiveness in comorbid obesity pathology, primarily among patients with type 2 diabetes. Here was held an analysis of possible negative effects after surgical treatment for obesity, including secondary hyperparathyroidism, post-bariatric hypoglycemia, etc., as well as predictors of postoperative prognosis in relation on metabolic control among patients with obesity and type 2 diabetes